2021
DOI: 10.1101/2021.12.15.472842
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

RB1 loss triggers dependence on ESRRG in retinoblastoma

Abstract: Retinoblastoma (Rb) is a deadly childhood eye cancer that is classically initiated by inactivation of the RB1 tumor suppressor. Clinical management continues to rely on nonspecific chemotherapeutic agents that are associated with treatment resistance and toxicity. Here, we analyzed 103 whole exomes, 16 whole transcriptomes, 5 single-cell transcriptomes, and 4 whole genomes from primary Rb tumors to identify novel Rb dependencies. Several recurrent genomic aberrations implicate estrogen-related receptor gamma (… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 72 publications
0
4
0
Order By: Relevance
“…Using pathway analysis, Field et al . observed that some secondary mutations could be connected in a protein interaction network that included the estrogen-related receptor ESRRG, which in turn was implicated in the retinoblastoma cell hypoxic response 14 . ESRRG- and hypoxic response-related ontologies were not enriched in our over-representation analyses or in an Ingenuity pathway analysis of the 542 somatic variants, though this could relate to deficiencies in ontology enrichment databases.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Using pathway analysis, Field et al . observed that some secondary mutations could be connected in a protein interaction network that included the estrogen-related receptor ESRRG, which in turn was implicated in the retinoblastoma cell hypoxic response 14 . ESRRG- and hypoxic response-related ontologies were not enriched in our over-representation analyses or in an Ingenuity pathway analysis of the 542 somatic variants, though this could relate to deficiencies in ontology enrichment databases.…”
Section: Discussionmentioning
confidence: 99%
“…In line with this finding, Field et al . have proposed that BCOR represses ESRRG1 to enable a hypoxic survival response, a function that would have no advantage in the hyperoxic tissue culture setting 14 . CHLA-VC-RB cell lines also had over-representation of ATM, SPRED1 , and PYHIN1 variants related to the p53-mediated DNA damage response.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations